Structural variants in 3000 rice genomes - Fuentes, Roven Rommel; Chebotarov, Dmytro; Duitama, Jorge; Smith, Sean; Hoz, Juan Fernando de la; Mohiyuddin, Marghoob; Wing, Rod A.; McNally, Kenneth L.; Tatarinova, Tatiana; Grigoriev, Andrey; Mauleon, Ramil; Alexandrov, Nickolai (Cold Spring Harbor Laboratory, 2019)
Investigation of large structural variants (SVs) is a challenging yet important task in understanding trait differences in highly repetitive genomes. Combining different bioinformatic approaches for SV detection, we analyzed whole-genome sequencing data from 3000 rice genomes and identified 63 million individual SV calls that grouped into 1.5 million allelic variants. We found enrichment of long SVs in promoters and an excess of shorter variants in 5′ UTRs. Across the rice genomes, we identified regions of high SV frequency enriched in stress response genes. We demonstrated how SVs may help in finding causative variants in genome-wide association analysis. These new insights into rice genome biology are valuable for understanding the effects SVs have on gene function, with the prospect of identifying novel agronomically important alleles that can be utilized to improve cultivated rice.